2021
DOI: 10.1093/mnras/stab3523
|View full text |Cite
|
Sign up to set email alerts
|

MUSE spectroscopy of planetary nebulae with high abundance discrepancies

Abstract: We present MUSE deep integral-field unit spectroscopy of three planetary nebulae (PNe) with high abundance discrepancy factors (ADF > 20): NGC 6778, M 1–42 and Hf 2–2. We have constructed flux maps for more than 40 emission lines, and use them to build extinction, electron temperature (Te), electron density (ne), and ionic abundances maps of a number of ionic species. The effects of the contribution of recombination to the auroral [N ii] and [O ii] lines on Te and the abundance maps of low-ionization sp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
16
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 93 publications
4
16
1
Order By: Relevance
“…Alternatively, large abundance discrepancies in PNe could be linked to binary central stars (Corradi et al 2015;Jones et al 2016;Bautista & Ahmed 2018;Wesson et al 2018;Jacoby et al 2020;García-Rojas et al 2022). In particular, Corradi et al (2015) found ADFs higher than 50 in the PNe Abell 46 and Ou 5 surrounding post common-envelope binary stars.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, large abundance discrepancies in PNe could be linked to binary central stars (Corradi et al 2015;Jones et al 2016;Bautista & Ahmed 2018;Wesson et al 2018;Jacoby et al 2020;García-Rojas et al 2022). In particular, Corradi et al (2015) found ADFs higher than 50 in the PNe Abell 46 and Ou 5 surrounding post common-envelope binary stars.…”
Section: Discussionmentioning
confidence: 99%
“…This discrepancy in abundances is associated to a combination of the different extinction, physical conditions, atomic data sets and ICFs adopted. A more detailed analysis of such differences has been presented in García-Rojas et al (2022). All chemical abundances derived from the pseudo-slits and the central region (Table 6) show small variations, within their uncertainties.…”
Section: The Case Study Of Ngc 6778 With Cor Muse Datamentioning
confidence: 91%
“…These advances have boosted the number of works devoted to spatially resolved studies of planetary nebulae (PNe) using IFS over the last decade; some representative examples of these studies are, e. g. Tsamis et al (2008), Monteiro et al (2013), Ali et al (2016), Walsh et al (2016), Walsh et al (2018), Ali & Dopita (2019), Monreal-Ibero & Walsh (2020), Akras et al (2020a), andGarcía-Rojas et al (2022).…”
mentioning
confidence: 99%
“…A number of integral field unit (IFU) spectrographs on modest telescopes, such as the Wide Field Spectrograph (WiFeS [24,25]) on the Australian National University (ANU) 2.3-m telescope have made it possible to constrain the kinematic and ionization properties of several PNe [26][27][28][29][30][31][32]. Moreover, the Multi Unit Spectroscopic Explorer (MUSE) and the VIsible Multi-Object Spectrograph (VIMOS) on the European Southern Observatory's (ESO) Very Large Telescope (VLT) have recently enabled the constraint of the ionization structures of some PNe [33][34][35][36]. IFU spectroscopy allows us to spatially resolve the physical and kinematic properties of PNe, which is an important step toward understanding their morphological features in different ionization stratification layers.…”
Section: Introductionmentioning
confidence: 99%